The effects of state ideology, politics, educational policies and philosophy on the science curricula of primary education 1919-1938 - Sezen, Aslı. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2007., 2007)
The aim of this study is to analyze the curricular changes in the area of science education at the primary level during the period of Atatürk (1919-1938) with the Yıldıran’s “Hierarchical Model of Factors Affecting Curricula (2006)”. According to this model, state ideology and politics influence educational policies, and these affect the educational philosophy underlying the curricula of the era. The thesis uses both historical and qualitative analyses. Historical analysis was used to explain the state ideology and politics, and educational policies of the period. For the analysis of the reports of the Scientific Council Meetings and foreign expert reports, inductive qualitative analyses were utilized. Finally, the science curricula were examined via deductive qualitative analysis. In conclusion, the state ideology of the period was formed by the six principles of Atatürk: Republicanism, Nationalism, Populism, Étatisme, Laicism, and Reformism (Revolutionism). The educational policies were national, rational, pragmatic, egalitarian, and humanistic. The educational philosophy was the Pragmatism of John Dewey in his concept of progressive education. The three science curricula of 1924, 1926 and 1936 were based on experiential learning theory, the teaching methods being observation, investigation, and experimentation. The curricula had detailed content in primary school science aimed at meeting practical local needs as well as preparing for further education. Objectives were not specified but could be inferred as content related (topical), student or teacher activities. There were no evaluation procedures suggested due to lack of theory in the area at the time.
Keywords: Science -- Study and teaching (Primary) -- Turkey.; Science -- Study and teaching -- Curricula.; Science -- Study and teaching -- Turkey -- History.; Education -- Turkey -- History.